2007
DOI: 10.1097/01.tp.0000251923.14697.f5
|View full text |Cite
|
Sign up to set email alerts
|

Increased Prevalence of Gastrointestinal Symptoms Associated with Impaired Quality of Life in Renal Transplant Recipients

Abstract: GI symptoms are associated with impaired HRQoL in the renal transplant population. Managing GI symptoms by careful choice of immunosuppressants should be a focus for improving HRQoL in renal transplant recipients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
69
2
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(85 citation statements)
references
References 52 publications
10
69
2
4
Order By: Relevance
“…iarrhea is a frequent complication in kidney transplant recipients (1)(2)(3)(4)(5)(6). Although diarrhea is often considered to be benign, severe episodes can cause dehydration with weight loss, high creatinine levels, and a fluctuation in serum immunosuppressive drug concentrations, resulting in a significant increase in mortality and morbidity and a poorer functional prognosis for the graft (1,2,6).…”
mentioning
confidence: 99%
“…iarrhea is a frequent complication in kidney transplant recipients (1)(2)(3)(4)(5)(6). Although diarrhea is often considered to be benign, severe episodes can cause dehydration with weight loss, high creatinine levels, and a fluctuation in serum immunosuppressive drug concentrations, resulting in a significant increase in mortality and morbidity and a poorer functional prognosis for the graft (1,2,6).…”
mentioning
confidence: 99%
“…Many previous studies confirmed that GI symptoms are the most prevalent in the early period after kidney transplant and may adversely affect the quality of life of transplant recipients. 2 Despite this confirmation, it was demonstrated that GI symptoms are underdiagnosed by the doctors in the general population as well as in kidney transplant recipients. 20,21 In contrast to the early period after transplant, little is known about the patterns, causes, and consequences of GI symptoms in the longer term after kidney transplant in clinically and biochemically stable patients.…”
Section: Discussionmentioning
confidence: 99%
“…Tacrolimus has been associated with an increased risk of diarrhea (odds ratio of 1.7; 95% confidence interval, 1.4-2.0) and constipation (odds ratio of 1.3; 95% confidence interval, 1.1-1.6). 2,10 In contrast, another calcineurin inhibitor, cyclosporine, has been found to induce constipation in renal transplant recipients. 10 It has been demonstrated that patients who are treated with tacrolimus have more frequent occurrences of diarrhea, dyspepsia, and vomiting compared with patients treated with cyclosporine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence and severity of GI side effects, among transplant recipients, appear to be associated with lower quality of life [107]. These had often been underestimated by the treating clinicians as shown in a survey conducted by Ekberg et al [108,109]. Table 5 summarizes the discontinuation rate among patients treated with mTOR-I, together with the commonly encountered side effects.…”
Section: Safety Of Mtor-i Protocols In Kidney Transplantationmentioning
confidence: 99%